European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB): An Update on the Pediatric CEUS Registry on Behalf of the “EFSUMB Pediatric CEUS Registry Working Group” - Dietrich, Christoph F.; Augustiniene, Rasa; Batko, Tomasz; Cantisani, Vito; Cekuolis, Andrius; Deganello, Annamaria; Dong, Yi; Franke, Doris; Harkanyi, Zoltan; Humphries, Paul D.; Jędrzejczyk, Maciej; Jüngert, Jörg; Kinkel, Horst; Koller, Orsolya; Kosiak, Wojciech; Kunze, Christian; Ljutikov, Anoushka; Madzik, Jaroslaw; Mentzel, Hans-Joachim; Piskunowicz, Maciej; Rafailidis, Vasileios; Schreiber-Dietrich, Dagmar; Sellars, Maria E.; Stenzel, Martin; Taut, Heike; Yusuf, Gibran T.; Sidhu, Paul S. (Ultraschall in der Medizin - European Journal of Ultrasound, 2021)
The European Federation of Ultrasound in Medicine and Biology (EFSUMB) created the “EFSUMB Pediatric Registry” (EFSUMB EPR) with the purpose of collecting data regarding the intravenous application of pediatric contrast-enhanced ultrasound (CEUS). The primary aim was to document the current clinical practice and usefulness of the technique and secondarily to assess CEUS safety in children. We issue the preliminary results of this database and examine the overall practice of CEUS in children in Europe.
Keywords: guideline; SonoVue; safety; pediatrics